Ethical and Legal Analysis of Artificial Intelligence Systems in Law Enforcement with a Study of Potential Human Rights Violations in Indonesia - Zuwanda, Zulkham Sadat; Lubis, Arief Fahmi; Solapari, Nuryati; Sakmaf, Marius Supriyanto; Triyantoro , Andri (Eastasouth Institute, 2024)
This research examines the ethical and legal implications of deploying Artificial Intelligence (AI) systems in law enforcement, with a particular focus on potential human rights violations in Indonesia. Utilizing a normative analysis approach, the study evaluates existing ethical frameworks, legal principles, and human rights standards to assess the governance and implications of AI-driven policing. Key findings indicate significant ethical concerns, including bias, discrimination, lack of transparency, and privacy violations. The legal analysis reveals gaps in Indonesia’s regulatory framework, highlighting the need for specific legislation to address AI’s complexities. Human rights implications, such as threats to privacy, freedom of expression, and equality, are critically analyzed. Comparative case studies from other jurisdictions provide empirical insights and underscore the importance of robust ethical and legal frameworks. The research proposes several recommendations, including the establishment of clear ethical guidelines, strengthening legal frameworks, enhancing transparency and accountability, promoting public engagement, and conducting regular impact assessments to ensure responsible AI governance in law enforcement. This study aims to contribute to the development of ethical AI governance frameworks and inform policy recommendations for responsible AI deployment in law enforcement practices.